Influence of Drying Temperature on the Different Thermodynamic Parameters during the Indirect Convective Solar Drying of Crocus sativus L. Of Morocco Thin-Layer Solar Drying of Moroccan Saffron - Khadija Oubella; Hind Mouhanni; Younes Bahammou; Ali Idlimam; Abdelkader Lamharrar; Abdelaziz Bendou (The Scientific World Journal)
This work deals with the study of the drying kinetics of Crocus sativus L. using convective solar drying. The main objective was to identify the influence of airflow drying temperatures for ambient air temperature ranged between 15.6 and 18.9°C, and a relative humidity between 24.4 and 46.5%. The equilibrium moisture content varies from 0.09 to 0.06 (% d.b), respectively, for drying air temperatures 35–50°C. The airflow velocity was about 0.2 m s−1, which implied establishing a phenomenological diffusion model of the water within the matrix. Empirical models were also determined as well as a polynomial equation (order 3) of the characteristic drying curve. The Midilli–Kucuk model was found to be the best to describe the experimental drying curves of Crocus sativus L. The effective moisture diffusivity ranged between 0.87 and 1.46 10−11 m2 s−1 for airflow temperature 35 and 50°C, while the average activation energy was calculated as 28.76 kJ mol−1. The increase in temperature decreases the total energy consumption which varies, respectively, from 3.211 to 2.681 kWh.